A Software Synchronization Method for High-Frequency Circulating Current in Multiple Inverter Parallel Systems - Wenping Zhang; Yiming Wang; Po Xu; Yiming Wang; Ke Ma; Yongheng Yang (IEEE Access)
To increase system power, multiple inverters are connected in parallel. However, if multiple inverters are connected in parallel but without carrier synchronization, it is possible to generate both high-frequency circulating current at the switching frequency and excessive ground current. To avoid high-frequency circulating current problems caused by unsynchronized carriers, the traditional solution is to synchronize them. Currently, the majority of carrier synchronization techniques are hardware based. This paper proposes a novel software synchronization method for multi-inverter parallel systems, eliminating the need for additional hardware. First, a parallel inverter system is modelled, and high-frequency circulating current analysis is performed. The high-frequency circulating current in the presence of an unsynchronized carrier is computed. The circulating current under unsynchronized carriers is quantitatively calculated. Next, a software synchronization mechanism for carriers in multi-inverter parallel systems is presented. Two different approaches are proposed: alignment at the zero crossing point and alignment at the peak point. The concept and implementation of these two options are thoroughly explained. Finally, the experiment is implemented and results show that the proposed method can achieve full carrier synchronization and significantly reduces the circulating current.